Inhibiting EGFR/HER-2 ameliorates neuroinflammatory responses and the early stage of tau pathology through DYRK1A - Kim, Jieun; Kim, Su-Jin; Jeong, Ha-Ram; Park, Jin-Hee; Moon, Minho; Hoe, Hyang-Sook (Frontiers in Immunology, 2022)
The FDA-approved EGFR/HER2 inhibitor varlitinib inhibits tumor growth and is used in cancer treatment. However, the neuroinflammatory response associated with EGFR/HER2 and its underlying mechanism have not been elucidated. This study evaluates the impact of varlitinib on LPS- and tau-mediated neuroinflammatory responses for the first time. In BV2 microglial cells, varlitinib reduced LPS-stimulated il-1β and/or inos mRNA levels and downstream AKT/FAK/NF-kB signaling. Importantly, varlitinib significantly diminished LPS-mediated microglial nlrp3 inflammasome activation in BV2 microglial cells. In primary astrocytes, varlitinib downregulated LPS-evoked astroglial il-1β mRNA levels, AKT signaling, and nlrp3 inflammasome activation. In LPS-treated wild-type mice, varlitinib significantly reduced LPS-stimulated glial activation and IL-1/NLRP3 inflammasome formation. Moreover, varlitinib significantly reduced micro- and astroglial activation and tau hyperphosphorylation in 3-month-old tau-overexpressing PS19 mice by downregulating tau kinase DYRK1A levels. However, in 6-month-old tau-overexpressing PS19 mice, varlitinib only significantly diminished astroglial activation and tau phosphorylation at Thr212/Ser214. Taken together, our findings suggest that varlitinib has therapeutic potential for LPS- and tau-induced neuroinflammatory responses and the early stages of tau pathology.